Effect of calcium and potassium oxide addition on the viscosity and fragility of a calcium aluminosilicate melt - Sukenaga, Sohei; Gueguen, Yann; Celarie, Fabrice; Rouxel, Tanguy; Tashiro, Masanori; Yoshida, Shinichiro; Saito, Noritaka; Nakashima, Kunihiko; Shibata, Hiroyuki (Journal of the American Ceramic Society, 2024)
Fragility is commonly quantified as the magnitude of change in viscosity at a temperature close to the glass transition temperature (Tg). It is a critical characteristic of melts used in scientific and industrial applications. The fragility of silicate melts generally increases with the depolymerization of silicate anions upon the addition of alkali or alkaline earth oxides. However, the effects of oxide additives on the fragility of aluminosilicate melts remain unclear. In this study, the effect of CaO or K2O addition on the viscosity of the 36CaO–51SiO2–13Al2O3 (mol.%) melt for the wide viscosity range of 10−1–1012 Pa s was studied. The relationship between the logarithmic viscosity and Tg‐scaled temperature indicated that the melt fragility increased with the addition of CaO, whereas the addition of K2O reduced the fragility when the additive content of CaO or K2O was less than 10.8 mol.%. The effect of the addition of K2O on fragility cannot be explained by the depolymerization of silicate anions alone. Raman and 27Al nuclear magnetic resonance spectroscopies of the glasses indicated that a decrease in the level of distortion of the AlO4 tetrahedra decreased the fragility of the aluminosilicate melt.